Topics in abstract algebra - Sen M K; Ghosh Shamik; Mukhopadhyay Parthasarathi (Hyderabad Universities Press, 2004)
The 1st chapter covers the algebra of sets, binary relations, with special emphasis on the congruence relation on the set of integers. Chapter 2 contains algebraic theories on integers,divisibility properties, mathematical induction methods, theory on pr
Keywords: Abstract algebra